PEMBUATAN E-COMMERCE PADA RAJA KOMPUTER MENGGUNAKAN BAHASA PEMROGRAMAN PHP DAN DATABASE MYSQL - Hermiati, Reza; Asnawati, Asnawati; Kanedi, Indra (UNIVED Press, 2021)
Raja Computer Shop Bengkulu is a computer shop that provides laptops, computers and computer accessories. The Bengkulu Raja Computer Store still applies manual shopping procedures or customers must come directly to the store. As well as manual systems such as recording data and sales transactions. To solve the problems above, increase sales and reach a wider market share. Raja Computer Shop Bengkulu uses technology in its marketing and sales strategy by implementing E-Commerce. For data modeling, a structured method is used, namely Entity Relationship Diagram (ERD) to describe the data model and Data Flow Diagram (DFD) to describe the functional model. This E-commerce application can help customers to get information about products offered by the No Way Distro, as well as make it easier for customers to order a product, and can help increase sales for the Bengkulu Raja Computer Store.